Analisis Velocity Model Building Pada Pre Stack Depth Migration Untuk Penggambaran Struktur Bawah Permukaan Daerah â€xâ€ - Triarto, Yose Rizal; Danusaputro, Hernowo; Harmoko, Udi (BERKALA FISIKA, 2010)
Pre Stack Depth Migration method has been carried out for 2D seismic reflection data on Line KPH-11807 at â€œXâ€ area. This method was chosen for reconstruction geology features and imaging the subsurface structure. Based on previous investigation which done October, 2004-January, 2005, Line KPH-11807 at â€œXâ€ area was a potential development as hydrocarbon prospect area which complex geology structure and strong lateral velocity variations. In the same area has been done previously with Pre Stack Time Migration by Elnusa Geosains, PT. Therefore the result of the PSDM can be compared to PSTM method. Seismic section with complex geology structure and/or strong lateral velocity variations area, which often there are at seismic data migrated stack can be overcome using an accurate velocity model. Velocity model building with the IVMB (interval velocity model building) concept consist of the coherency inversion and global tomography yield the right subsurface geological model. Hereinafter the velocity model will be used for the PSDM (pre stack depth migration) process. Result of PSDM shows a significant image enhancement, able to assure the reflection pattern at the horizons with strong lateral velocity variations and give the more coherence resolution compared with Pre Stack Time Migration seismic data. This study is very valuable in building exploration concept and development of the area, especially in a complex structure with strong lateral velocity variations. Â Keywords: PSDM, velocity model building.